Structural Analysis of Higher Education Institutions' Research Introductions - Salvador Dela Pena III (JPAIR Institutional Research Journal)
In writing a research article, the introduction seems to be the hardest part to write. In fact, many research articles are found to have insufficient introduction, lacking some important elements of a quality introduction. Hence, this study was conducted to assess through content analysis the quality of the introduction of published articles authored by researchers in Mindanao. Fifty samples were analyzed based on the widely accepted standards for writing the introduction. Descriptive statistics was used in the analysis of the data. Findings reveal that most of the introduction samples had missing elements of a quality introduction. The most missed out element was a statement establishing a gap to indicate academic importance, followed by a statement of the practical importance of the study and general statement of the problem of the study. As to the structure of the introduction, most of the samples followed the standard structure, proceeding from general to specific statements. The findings imply that many published research articles by researchers in Mindanao have introductions that do not meet the standards for writing quality introduction, hence the need to reorient researchers to the basics of writing a good introduction.